Individual differences in responses to nicotine: tracking changes from adolescence to adulthood - Li Ming; Mead Alexa; Bevins Rick A (Acta Pharmacologica Sinica, 2016)
Aim: The present study determined the extent to which individual differences in responses to the psychostimulating effect of nicotine during adolescence predict similar individual differences during adulthood in rats. We also examined the possible long-term effects of adolescent nicotine exposure on adult prepulse inhibition (PPI) of the acoustic startle response, a measure of sensorimotor gating ability. Methods: During the adolescent phase, rats were administered saline, 0.10, 0.40, or 0.60 mg/kg nicotine via subcutaneous injections for 8 days, and motor activity was measured daily. During the adult phase, these rats were treated with the same nicotine dose as in adolescence for 8 additional days. The adolescent saline rats (now adults) were subdivided into four groups and administered saline, 0.10, 0.40, or 0.60 mg/kg nicotine, respectively. PPI was assessed 12 days after the last nicotine treatment. Results: During both phases, nicotine increased motor activity across test days in a dose-dependent manner. Motor activity of rats treated with nicotine during adolescence was positively correlated with the activity recorded from the same rats during adulthood. In both phases, there were profound individual differences in the responses to the nicotine treatments. In addition, adolescent rats treated with nicotine did not show decreased motor response to the initial exposure to nicotine. Finally, adolescent exposure to nicotine at 0.4 mg/kg, but not adulthood exposure to the same dose of nicotine, produced a robust disruption of PPI, with individual rats showing different degrees of PPI disruption. Conclusion: These findings suggest that adolescent rats have increased sensitivity to the psychostimulating effect and decreased sensitivity to the aversive effect of nicotine. Also, nicotine exposure during adolescence may have long-term detrimental effects on sensorimotor gating ability.